Experimental and theoretical studies of the N(2D) + H2 and D2 reactions. Issue 41 (14th October 2020) - Nuñez-Reyes, Dianailys; Bray, Cédric; Hickson, Kevin M.; Larrégaray, Pascal; Bonnet, Laurent; González-Lezana, Tomás
Abstract : This study reports the first kinetic measurements of the N( 2 D) + H2, D2 reactions below 200 K. Abstract : This study reports the results of an experimental and theoretical investigation of the N( 2 D) + H2 and N( 2 D) + D2 reactions at room temperature and below. On the experimental side, a supersonic flow (Laval nozzle) reactor was employed to measure rate constants for these processes at temperatures as low as 127 K. N( 2 D) was produced indirectly by pulsed laser photolysis and these atoms were detected directly by pulsed laser induced fluorescence in the vacuum ultraviolet wavelength region. On the theoretical side, two different approaches were used to calculate rate constants for these reactions; a statistical quantum mechanical (SQM) method and a quasi-classical trajectory capture model including a semi-classical correction for tunneling (SC-Capture). This work is described in the context of previous studies, while the discrepancies between both experiment and theory, as well as between the theoretical results themselves are discussed.